Ascorbate depletion increases growth and metastasis of melanoma cells in vitamin C deficient mice - Cha, J.; Roomi, M.W.; Ivanov, V.; Kalinovsky, T.; Niedzwiecki, A.; Rath, M. (Experimental Oncology, 2011)
Aim: Our main objective was to determine the effect of ascorbate supplementation in mice unable to synthesize ascorbic acid (gulo KO) when challenged with murine B16FO cancer cells. Methods: Gulo KO female mice 36–40 weeks of age were deprived of or maintained on ascorbate in food and water for 4 weeks prior to subcutaneous injection of 2.5×106 B16FO murine melanoma cells in the right flank of mice. A control group of wild type mice were also injected with the melanoma cells and maintained on a regular murine diet. Mice were continued on their respective diets for another 2 weeks after injection. The mice were then sacrificed, blood was drawn and their tumors were measured, excised and processed for histology. Results: Mean weight of animals decreased significantly (30%, p < 0.0001) in the ascorbate-restricted group but increased slightly, but insignificantly, in the ascorbate-supplemented group. The mean tumor weight in ascorbate supplemented mice was significantly reduced (by 64%, p = 0.004) compared to tumor weight in ascorbate-deprived gulo mice. The mean tumor weight of wild type mice did not differ significantly from the ascorbate-supplemented mice. Gulo KO mice supplemented with ascorbate developed smaller tumors with more collagen encapsulation and fibrous capsule interdigitation, while gulo KO mice deprived of ascorbate hosted large tumors with poorly defined borders, showing more necrosis and mitosis. Ascorbate supplementation of gulo KO mice resulted in profoundly decreased serum inflammatory cytokine IL-6 (90% decrease, p = 0.04) and IL-1β (62% decrease) compared to the levels in gulo KO mice deprived of ascorbate. Conclusion: Ascorbate supplementation modulated tumor growth and inflammatory cytokine secretion as well as enhanced encapsulation of tumors in scorbutic mice.